Catalytic layer-loaded carbon felt electrode for flow battery electrode as well as preparation method and application of catalytic layer-loaded carbon felt electrode
By loading metal/nitrogen composite materials on the electrode of the liquid flow battery to form a composite multi-stage pore structure, the problems of insufficient conductivity and catalytic performance of the existing electrode materials are solved, and the electrochemical performance of the liquid flow battery is significantly improved. It is suitable for large-scale Large-scale energy storage technology.
Patent Information
- Application Number
- CN202310731990.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-20
- Publication Date
- 2024-12-27
AI Technical Summary
The conductivity and catalytic performance of existing liquid flow battery electrode materials affect the energy efficiency and stability of the battery. Especially the application of polyacrylonitrile-based carbon fiber felt in liquid flow battery electrodes has strong hydrophobicity on the surface of the material and electrolyte. Problems of inability to infiltrate well and poor electrocatalytic activity.
The metal/nitrogen composite material is used to load the carbon felt substrate, and the carbon felt electrode with a catalytic layer is prepared by spraying method to form a composite multi-stage pore structure to improve the conductivity and catalytic performance of the electrode. The method includes reacting the transition metal salt and organic ligand to form a metal organic framework material, and then forming a spinning solution with the polymer powder, preparing a MOF-based nanofiber membrane by high-pressure electrospinning, and performing pre-oxidation and heat treatment to generate a metal/ Nitrogen co-doped integrated composite material, loaded on the carbon felt matrix.
The electrochemical performance of the flow battery is significantly improved, including energy efficiency, voltage efficiency and Coulomb efficiency, ensuring high catalytic activity and low resistance of the electrode material, and is suitable for the application of large-scale energy storage technology.
Smart Images

Figure CN119208640A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of liquid flow batteries and relates to a carbon felt electrode with a catalytic layer for a liquid flow battery electrode and a preparation method and application thereof. Background Art
[0002] The traditional energy supply structure mainly relies on fossil energy, but it is no longer in line with the sustainable development laws of human society. At present, the global energy consumption structure is accelerating its transformation towards low-carbonization, and the large-scale use of renewable energy will be the basic trend of future energy development. Renewable energy such as solar energy, wind energy, hydropower and biomass energy has broad development prospects, but due to its non-steady-state characteristics such as volatility and intermittency, it will be affected by factors such as weather conditions. In this case, energy storage technology has the natural advantage of peak load regulation, which helps to improve the ability of the power grid to accept clean energy and solve the problems of power grid security and stability caused by large-scale clean energy access.
[0003] Liquid flow batteries have become one of the most promising large-scale energy storage technologies due to their high energy conversion efficiency, large storage capacity, freedom of site selection, deep discharge, long service life, safety and environmental protection. However, polyacrylonitrile-based carbon fiber felt, a key material for liquid flow batteries, is currently mainly used for fire-resistant and heat-insulating materials. Its specifications and surface properties are not processed and produced for liquid flow battery electrode materials, so it is difficult to meet the performance requirements of liquid flow batteries. If it is used directly as a liquid flow battery electrode, there will be a series of problems, such as strong hydrophobicity of the material surface, poor infiltration of the electrolyte, and poor electrocatalytic activity.
[0004] Therefore, it is very necessary to develop targeted electrode materials for the requirements of flow batteries. This can not only improve the energy efficiency and energy density of flow battery products, but also has important significance for promoting the development of advanced electrochemical energy storage technology and the research and development of clean energy diversification. One possible solution is to combine MOF materials with traditional electrode materials to prepare electrode materials with composite multi-level pore structures. MOF materials are assembled from metal ions and organic ligands, and have extremely high specific surface area, rich active sites, adjustable pore structure, good stability, and easy modification and functionalization, so they have great potential. For example, Chinese patent CN111785978B provides a method for in-situ generation of MOF on the surface of electrospun fiber filaments, and obtaining porous electrodes by pre-oxidation and carbonization. However, this method has the problem of insufficient conductivity and catalytic performance, which may affect the energy efficiency of the assembled battery. Therefore, in the process of combining MOF materials with traditional electrode materials, it is necessary to further study and optimize the conductivity and catalytic performance of the materials to improve the energy efficiency of flow batteries. Summary of the invention
[0005] In view of the above-mentioned defects existing in the prior art, the purpose of the present invention is to provide a carbon felt electrode loaded with a catalytic layer for a liquid flow battery electrode, and a preparation method and application thereof, which can solve the problems of insufficient conductivity and catalytic performance existing in the prior art. The present invention obtains a carbon felt electrode loaded with a catalytic layer by loading a metal / nitrogen composite material with catalytic effect onto a carbon felt substrate, which can enable the liquid flow battery electrode to have higher electrocatalytic activity and cross-resistance, thereby effectively improving the electrochemical performance of the liquid flow battery.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] The first aspect of the present invention provides a method for preparing a carbon felt electrode loaded with a catalytic layer for a liquid flow battery electrode, wherein a metal / nitrogen composite material is dispersed in an organic alcohol solution to obtain a mixed liquid, and the mixed liquid is loaded on a carbon felt substrate by a spraying method, and after vacuum drying, a carbon felt electrode loaded with a catalytic layer for a liquid flow battery electrode is obtained.
[0008] Preferably, the mass ratio of the metal / nitrogen composite material to the volume ratio of the organic alcohol solution is 0.02-0.04 g / ml; and / or
[0009] The organic alcohol is selected from one of isopropanol, methanol, ethanol and n-butanol; and / or
[0010] The carbon felt substrate is selected from one of PAN-based carbon fiber felt, asphalt-based carbon fiber felt, and viscose-based carbon fiber felt.
[0011] Preferably, the process parameters of the spraying are: nozzle diameter is 0.2-0.6 mm, spraying amount is 0.05-0.3 g / min, and spraying time is 20-80 min.
[0012] Preferably, the thickness of the carbon felt substrate is 2 to 5 mm; and / or
[0013] The loading amount of the metal / nitrogen composite material on the carbon felt electrode supporting the catalytic layer for the liquid flow battery electrode is 5 to 15 mg / cm 2 .
[0014] Preferably, the metal / nitrogen composite material comprises the following steps:
[0015] S1, dissolving a transition metal salt and an organic ligand in a solvent for reaction, and then sequentially centrifuging, washing and vacuum drying to obtain a metal organic framework material;
[0016] S2, adding the metal organic framework material and polymer powder obtained in step S1 into an organic solvent, stirring until uniformly dissolved to form a spinning solution, and preparing a MOF-based nanofiber membrane by high-voltage electrospinning;
[0017] S3, pre-oxidizing the MOF-based nanofiber membrane, heat-treating it with melamine powder, grinding it and breaking it, to obtain a metal / nitrogen co-doped integrated composite material of in-situ grown carbon nanotubes, that is, a metal / nitrogen composite material.
[0018] Preferably, in step S1:
[0019] The transition metal salt is selected from one or more of zinc nitrate, zinc sulfate, zinc chloride, zinc acetate, cobalt nitrate, cobalt sulfate, cobalt chloride, cobalt acetate, nickel nitrate, nickel sulfate, nickel chloride, nickel acetate, ferric nitrate, ferric sulfate, ferric chloride, and ferric acetate; and / or
[0020] The organic ligand is selected from one or more of 2-methylimidazole, 4,4'-bipyridine, o-phenanthroline, 2,3,5-pyridine triacid and terephthalic acid: and / or
[0021] The solvent is selected from one or more of methanol, water, ethanol and dimethylformamide; and / or
[0022] The transition metal salt and the organic ligand are dissolved in 3 to 20 parts by weight of a solvent at a weight ratio of 1:0.5 to 1:5; and / or
[0023] The reaction temperature is 20-200° C., and the reaction time is 2-48 hours.
[0024] Preferably, in step S1:
[0025] The transition metal salt and the organic ligand are dissolved in 5 to 15 parts by weight of a solvent at a weight ratio of 1:1 to 1:3; and / or
[0026] The reaction temperature is 20-150° C., and the reaction time is 6-36 hours.
[0027] Preferably, in step S2:
[0028] The polymer powder is selected from one or more of polyacrylonitrile, polyimide, polyvinylidene fluoride and polyvinyl pyrrolidone; and / or
[0029] The organic solvent is selected from one of dimethylformamide, dimethyl sulfoxide and dimethylacetamide; and / or
[0030] The metal organic framework material and the polymer powder are mixed in a weight ratio of 0.1:1 to 5:1 and then added to 1 to 10 parts by weight of an organic solvent; and / or
[0031] The stirring temperature is 20 to 100° C.; and / or
[0032] The diameter of the MOF-based nanofiber membrane is 50 to 800 nm.
[0033] Preferably, in step S2:
[0034] The metal organic framework material and the polymer powder are mixed in a weight ratio of 0.5:1 to 3:1 and then added to 2 to 5 parts by weight of an organic solvent; and / or
[0035] The stirring temperature is 40 to 80° C.; and / or
[0036] The diameter of the MOF-based nanofiber membrane is 100-600 nm.
[0037] Preferably, in step S3:
[0038] The pre-oxidation treatment process is carried out in an air atmosphere, the pre-oxidation temperature is 180 to 300° C., and the pre-oxidation time is 0.5 to 5 hours; and / or
[0039] The weight ratio of the pre-oxidized MOF-based nanofiber membrane to the melamine powder is 1:0.2 to 1:5; and / or
[0040] The heat treatment is carried out in a nitrogen atmosphere, the heat treatment temperature is 600 to 2500° C., and the heat treatment time is 0.5 to 4 hours; and / or
[0041] The heat treatment method of the pre-oxidized MOF-based nanofiber membrane and the melamine powder is one of uniform spreading, parallel arrangement and vertical arrangement; and / or
[0042] The length of the metal / nitrogen composite material is 1 to 60 μm.
[0043] Preferably, in step S3:
[0044] In the pre-oxidation treatment, the pre-oxidation temperature is 200 to 280° C. and the pre-oxidation time is 1 to 4 hours; and / or
[0045] The weight ratio of the pre-oxidized MOF-based nanofiber membrane to the melamine powder is 1:0.5 to 1:4; and / or
[0046] During the heat treatment, the heat treatment temperature is 800-2200° C. and the heat treatment time is 1-3 hours; and / or
[0047] The length of the metal / nitrogen composite material is 5 to 50 μm.
[0048] The second aspect of the present invention provides a carbon felt electrode for a liquid flow battery electrode carrying a catalytic layer, which is prepared according to the method for preparing a carbon felt electrode for a liquid flow battery electrode carrying a catalytic layer according to the first aspect of the present invention.
[0049] The third aspect of the present invention provides a use of a carbon felt electrode carrying a catalytic layer for a liquid flow battery electrode according to the second aspect of the present invention in a liquid flow battery.
[0050] Preferably, at a current density of 120 mA / cm 2 When the carbon felt electrode with a catalytic layer for the flow battery electrode has an energy efficiency of ≥83%, a voltage efficiency of ≥85%, and a coulombic efficiency of ≥95%; and / or
[0051] At a current density of 200 mA / cm 2 When the carbon felt electrode with a catalytic layer for the liquid flow battery electrode is used, the energy efficiency is ≥80%, the voltage efficiency is ≥82%, and the coulombic efficiency is ≥94%.
[0052] The carbon felt electrode with a catalytic layer for a flow battery electrode provided by the present invention and its preparation method and application have the following beneficial effects:
[0053] 1. The method of the present invention has low energy consumption and is easy to mass produce. The in-situ loaded carbon nanotubes on the catalytic layer of the prepared carbon felt electrode with a loaded catalytic layer greatly improve the conductivity of the electrode material, and have both metal / nitrogen dual-functional catalysis. When applied to liquid flow batteries, it has high electrocatalytic activity and low resistance, and can effectively improve the electrochemical performance of liquid flow batteries.
[0054] 2. The present invention utilizes metal organic framework to modify nano-carbon fiber to form a composite multi-level pore structure, enhance the infiltration of electrolyte, and simultaneously have a metal / nitrogen dual-functional catalytic effect, and loads the carbon felt electrode loaded with a catalytic layer on a carbon felt substrate to improve the electrocatalytic activity;
[0055] 3. The metal / nitrogen composite material used in the present invention in situ catalyzes the growth of carbon nanotubes at the metal sites on the surface of MOF-based nanofibers while carbonizing them, forming a three-dimensional network with the porous metal organic framework, providing a faster channel for the electron transfer process. While ensuring the mechanical strength, the metal / nitrogen composite material is loaded on the carbon felt matrix to obtain a carbon felt electrode loaded with a catalytic layer, which can greatly improve the conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0057] Figure 1 The present invention is a schematic flow diagram of a method for preparing a carbon felt electrode carrying a catalytic layer for a liquid flow battery electrode. DETAILED DESCRIPTION
[0058] In order to better understand the above technical solution of the present invention, the technical solution of the present invention is further described below in conjunction with embodiments.
[0059] Combination Figure 1 As shown, a method for preparing a carbon felt electrode with a catalyst layer for a liquid flow battery electrode of the present invention comprises dispersing a metal / nitrogen composite material in an organic alcohol solution to obtain a mixed solution, and using a spraying method to load the mixed solution on a carbon felt substrate, and obtaining a carbon felt electrode with a catalyst layer for a liquid flow battery electrode after vacuum drying. The mass ratio of the metal / nitrogen composite material to the volume of the organic alcohol solution is 0.02-0.04 g / ml; the organic alcohol is selected from one of isopropanol, methanol, ethanol, and n-butanol; the carbon felt substrate can be selected from one of PAN-based carbon fiber felt, asphalt-based carbon fiber felt, and viscose-based carbon fiber felt. The process parameters of the spraying are: the nozzle diameter is 0.2-0.6 mm, the spraying amount is 0.05-0.3 g / min, and the spraying time is 20-80 min. The thickness of the carbon felt substrate is 2-5 mm; the loading amount of the metal / nitrogen composite material on the carbon felt electrode with a catalyst layer is 5-15 mg / cm 2 .
[0060] Combination Figure 1 As shown, the metal / nitrogen composite material used above comprises the following steps:
[0061] S1, dissolving a transition metal salt and an organic ligand in a solvent for reaction, and then sequentially centrifuging, washing and vacuum drying to obtain a metal organic framework material;
[0062] Specifically, the transition metal salt and the organic ligand are dissolved in 3 to 20 parts by weight of a solvent (the total weight of the transition metal salt and the organic ligand is 1 part by weight) at a weight ratio of 1:0.5 to 1:5, and reacted at a reaction temperature of 20 to 200°C for 2 to 48 hours to obtain a precipitate, which is then centrifuged, washed and vacuum dried in sequence to obtain a metal organic framework material. Among them, the transition metal salt is selected from one or more of zinc nitrate, zinc sulfate, zinc chloride, zinc acetate, cobalt nitrate, cobalt sulfate, cobalt chloride, cobalt acetate, nickel nitrate, nickel sulfate, nickel chloride, nickel acetate, iron nitrate, iron sulfate, iron chloride, and iron acetate. The organic ligand is selected from one or more of 2-methylimidazole, 4,4'-bipyridine, o-phenanthroline, 2,3,5-pyridine triacid and terephthalic acid. The solvent is selected from one or more of methanol, water, ethanol, and dimethylformamide. In a preferred embodiment, the transition metal salt and the organic ligand are dissolved in 5 to 15 parts by weight of a solvent at a weight ratio of 1:1 to 1:3. The reaction temperature is 20 to 150° C. and the reaction time is 6 to 36 hours.
[0063] S2, adding the metal organic framework material and polymer powder obtained in step S1 into an organic solvent, stirring until they are uniformly dissolved to form a spinning solution, and preparing a MOF-based nanofiber membrane by high-voltage electrospinning;
[0064] Specifically, the metal organic framework material and the polymer powder obtained in step S1 are mixed in a weight ratio of 0.1:1 to 5:1, added to 1 to 10 parts by weight of an organic solvent (the total weight of the metal organic framework material and the polymer powder is 1 part by weight), stirred at 20 to 100°C until uniformly dissolved to form a spinning solution, and a MOF-based nanofiber membrane with a diameter of 50 to 800 nm is prepared by high-voltage electrospinning. Among them, the polymer powder is selected from one or more of polyacrylonitrile, polyimide, polyvinylidene fluoride, and polyvinyl pyrrolidone. The organic solvent is selected from one of dimethylformamide, dimethyl sulfoxide and dimethylacetamide. In a specific embodiment, the metal organic framework material and the polymer powder are mixed in a weight ratio of 0.5:1 to 3:1 and then added to 2 to 5 parts by weight of an organic solvent; the stirring temperature is 40 to 80°C. In a specific embodiment, the electrospinning process parameters are: the needle aperture is 0.3-2.0 mm, the syringe capacity is 5-500 ml, the spinning solution flow rate is 0.2-5 ml / hour, the roller speed is 100-1000 rpm, the voltage between the needle and the roller is 10-30 kV, the distance between the needle and the nanofiber membrane collecting plate on the roller is 10-30 cm, the spinning temperature is 20-50°C, and the spinning humidity is 20-70% RH. The diameter of the MOF-based nanofiber membrane prepared above is 100-600 nm.
[0065] S3, pre-oxidizing the MOF-based nanofiber membrane, heat-treating it with melamine powder, grinding and crushing it to obtain a metal / nitrogen co-doped integrated composite material of in-situ grown carbon nanotubes, namely a metal / nitrogen composite material.
[0066] Specifically, the MOF-based nanofiber membrane obtained in step S2 is pre-oxidized in an air atmosphere at 180-300°C for 0.5-5 hours, and then the pre-oxidized MOF-based nanofiber membrane and melamine powder are heat-treated in a nitrogen atmosphere at 600-2500°C for 0.5-4 hours at a weight ratio of 1:0.2-1:5, and after grinding and crushing, a metal / nitrogen co-doped integrated composite material of in-situ grown carbon nanotubes with a length of 1-60 μm is obtained, that is, a carbon felt electrode with a catalyst layer for a flow battery electrode. In the pre-oxidation treatment, the pre-oxidation temperature is 200-280°C, and the pre-oxidation time is 1-4 hours. During the heat treatment process, the weight ratio of the pre-oxidized MOF-based nanofiber membrane to the melamine powder is 1:0.5 to 1:4; the heat treatment method of the pre-oxidized MOF-based nanofiber membrane and the melamine powder is one of uniform spreading, parallel arrangement and vertical arrangement; the heat treatment temperature is 800 to 2200°C, and the heat treatment time is 1 to 3 hours. The length of the prepared metal / nitrogen composite material is 5 to 50 μm.
[0067] The present invention loads the above-mentioned metal / nitrogen composite material on a carbon felt substrate to obtain a carbon felt electrode loaded with a catalytic layer for a liquid flow battery electrode. The carbon felt electrode loaded with a catalytic layer has a large specific surface area and abundant active sites, and has a metal / nitrogen dual-functional catalytic effect, thereby improving the electrocatalytic activity of the electrode material and promoting the reaction activity of the redox electron pairs, thereby solving the electrode polarization problem and further improving the performance of the single cell.
[0068] The present invention also provides a carbon felt electrode carrying a catalytic layer for a liquid flow battery electrode, which is prepared according to the method for preparing the carbon felt electrode carrying a catalytic layer for a liquid flow battery electrode.
[0069] The present invention also provides an application of the above-mentioned carbon felt electrode with a catalytic layer for a flow battery electrode in a flow battery; the carbon felt electrode with a catalytic layer for a flow battery electrode is used at a current density of 120 mA / cm 2 When the current density is 200mA / cm 2 When the energy efficiency is ≥80%, the voltage efficiency is ≥82%, and the coulombic efficiency is ≥94%.
[0070] The carbon felt electrode loaded with a catalytic layer for a liquid flow battery electrode of the present invention, as well as its preparation method and application are further introduced below with reference to specific examples.
[0071] Example 1
[0072] A method for preparing a carbon felt electrode with a catalyst layer for a flow battery electrode according to this embodiment comprises the following steps:
[0073] (1) 100 g of zinc nitrate, 10 g of ferric chloride and 220 g of 2-methylimidazole were dissolved in 1700 g of methanol, reacted at 60° C. for 24 h, and a precipitate was obtained. The precipitate was washed by centrifugation three times, and vacuum dried at 60° C. to obtain Fe / Zn-MOFs (i.e., metal organic framework materials).
[0074] (2) Weigh 20 g of the Fe / Zn-MOFs obtained in step (1), 1 g of polyvinyl pyrrolidone and 9 g of polyacrylonitrile, add them to 100 g of dimethylformamide, stir at 60°C until uniformly dissolved to form a spinning solution, and prepare MOF-based nanofibers with a diameter of 200 nm by high-voltage electrospinning.
[0075] (3) The MOF-based nanofibers obtained in step (2) are pre-oxidized in an air atmosphere at 270° C. for 2 hours, and then melamine powder in a weight ratio of 1:2 is evenly sprinkled on the fibers, and heat-treated in a nitrogen atmosphere at 1500° C. for 2 hours. After grinding and crushing, a metal / nitrogen co-doped integrated composite material of in-situ grown carbon nanotubes with a length of 28 μm, i.e., a metal / nitrogen composite material, is obtained.
[0076] (4) Weigh 3 g of the metal / nitrogen composite material obtained in step (3) and disperse it in 100 mL of isopropanol solution. Use a spray gun with a nozzle diameter of 0.3 mm, a spraying amount of 0.2 g / min, and a spraying time of 60 min. Load the mixed solution onto a 6 cm×6 cm polyacrylonitrile-based carbon felt substrate with a thickness of 4.3 mm. After vacuum drying at 40° C., obtain an electrode material with a loaded catalytic layer. Assemble it into a single cell and perform a charge and discharge performance test: at a current density of 120 mA / cm 2 When the current density is increased to 200mA / cm 2 When the power consumption is 2.5%, the energy efficiency is 82.5%, the voltage efficiency is 86.7%, and the coulombic efficiency is 95.2%.
[0077] Example 2
[0078] A method for preparing a carbon felt electrode with a catalyst layer for a flow battery electrode according to this embodiment comprises the following steps:
[0079] (1) 100 g of cobalt nitrate and 130 g of 2-methylimidazole were dissolved in 2500 g of ethanol, and the mixture was reacted at 25° C. for 30 h to obtain a precipitate, which was washed by centrifugation three times and dried in vacuo at 60° C. to obtain Co-MOFs (i.e., metal organic framework materials).
[0080] (2) Weigh 20 g of the Co-MOFs obtained in step (1) and 12 g of polyacrylonitrile, add them to 100 g of dimethyl sulfoxide, stir at 50° C. until uniformly dissolved to form a spinning solution, and prepare MOF-based nanofibers with a diameter of 250 nm by high-voltage electrospinning.
[0081] (3) The MOF-based nanofibers obtained in step (2) are pre-oxidized in an air atmosphere at 250° C. for 1 hour, and then melamine powder and fibers are arranged in parallel at a weight ratio of 1:1.5, and heat-treated in a nitrogen atmosphere at 1800° C. for 1.5 hours. After grinding and crushing, a metal / nitrogen co-doped integrated composite material of in-situ grown carbon nanotubes with a length of 35 μm, i.e., a metal / nitrogen composite material, is obtained.
[0082] (4) Weigh 3 g of the metal / nitrogen composite material obtained in step (3) and disperse it in 100 mL of methanol solution. Use a spray gun with a nozzle diameter of 0.4 mm, a spraying amount of 0.25 g / min, and a spraying time of 45 min to load the mixed solution onto a 6 cm×6 cm polyacrylonitrile-based carbon felt material with a thickness of 3.8 mm. After vacuum drying at 40° C., an electrode material with a loaded catalytic layer is obtained. The electrode material is assembled into a single cell and the charge and discharge performance is tested: at a current density of 120 mA / cm 2 When the current density is increased to 200mA / cm 2 When the power consumption is 2.5W, the energy efficiency is 80.1%, the voltage efficiency is 84.9%, and the coulombic efficiency is 94.4%.
[0083] Example 3
[0084] A method for preparing a carbon felt electrode with a catalyst layer for a flow battery electrode according to this embodiment comprises the following steps:
[0085] (1) 100 g of nickel nitrate and 200 g of terephthalic acid were dissolved in 1900 g of dimethylformamide, and the mixture was reacted at 140° C. for 20 h to obtain a precipitate, which was washed by centrifugation three times and dried in vacuo at 60° C. to obtain Ni-MOFs (i.e., metal organic framework materials).
[0086] (2) Weigh 20 g of the Ni-MOFs obtained in step (1), 2 g of polyimide and 10 g of polyacrylonitrile, add them to 120 g of dimethylacetamide, stir at 70°C until uniformly dissolved to form a spinning solution, and prepare MOF-based nanofibers with a diameter of 300 nm by high-voltage electrospinning.
[0087] (3) The MOF-based nanofibers obtained in step (2) are pre-oxidized in an air atmosphere at 265° C. for 1.5 hours, and then melamine powder and fibers are arranged in parallel in a weight ratio of 1:1.8, and heat-treated in a nitrogen atmosphere at 2000° C. for 1 hour. After grinding and crushing, a metal / nitrogen co-doped integrated composite material of in-situ grown carbon nanotubes with a length of 40 μm, i.e., a metal / nitrogen composite material, is obtained.
[0088] (4) Weigh 3 g of the metal / nitrogen composite material obtained in step (3) and disperse it in 100 mL of ethanol solution. Use a spray gun with a nozzle diameter of 0.5 mm, a spraying amount of 0.15 g / min, and a spraying time of 60 min to load the mixed solution onto a 6 cm×6 cm polyacrylonitrile-based carbon felt material with a thickness of 3.2 mm. After vacuum drying at 40° C., an electrode material with a loaded catalytic layer is obtained. The electrode material is assembled into a single cell and the charge and discharge performance is tested: at a current density of 120 mA / cm 2When the current density is increased to 200mA / cm 2 When the energy efficiency is 82.3%, the voltage efficiency is 85.7%, and the coulombic efficiency is 96.0%.
[0089] Example 4
[0090] A method for preparing a carbon felt electrode with a catalyst layer for a flow battery electrode according to this embodiment comprises the following steps:
[0091] (1) 30 g of zinc sulfate, 10 g of ferric nitrate, 70 g of cobalt sulfate, 50 g of o-phenanthroline and 210 g of 2-methylimidazole were dissolved in 2100 g of methanol, reacted at 40° C. for 18 h to obtain a precipitate, which was centrifuged and washed three times. After vacuum drying at 60° C., Zn / Fe / Co-MOFs (i.e., metal organic framework materials) were obtained.
[0092] (2) Weigh 20 g of the Zn / Fe / Co-MOFs obtained in step (1), 3 g of polyvinylidene fluoride and 9 g of polyacrylonitrile, add them to 100 g of dimethylformamide, stir at 50°C until uniformly dissolved to form a spinning solution, and prepare MOF-based nanofibers with a diameter of 350 nm by high-voltage electrospinning.
[0093] (3) The MOF-based nanofibers obtained in step (2) were pre-oxidized in an air atmosphere at 245° C. for 1.8 hours, and then melamine powder and fibers in a weight ratio of 1:2.2 were vertically arranged and heat treated in a nitrogen atmosphere at 1500° C. for 2.5 hours. After grinding and crushing, a metal / nitrogen co-doped integrated composite material of in-situ grown carbon nanotubes with a length of 30 μm, i.e., a metal / nitrogen composite material, was obtained.
[0094] (4) Weigh 3 g of the metal / nitrogen composite material obtained in step (3) and disperse it in 100 mL of n-butanol solution. Use a spray gun with a nozzle diameter of 0.3 mm, a spraying amount of 0.12 g / min, and a spraying time of 70 min. Load the mixed solution onto a 6 cm×6 cm asphalt-based carbon felt material with a thickness of 3.2 mm. After vacuum drying at 40°C, obtain an electrode material with a loaded catalytic layer. Assemble it into a single cell and perform a charge and discharge performance test: at a current density of 120 mA / cm 2 When the current density is increased to 200mA / cm 2 When the power consumption is 2.5W, the energy efficiency is 81.7%, the voltage efficiency is 84.7%, and the coulombic efficiency is 96.4%.
[0095] Example 5
[0096] A method for preparing a carbon felt electrode with a catalyst layer for a flow battery electrode according to this embodiment comprises the following steps:
[0097] (1) 10 g of ferric sulfate, 100 g of cobalt acetate, 20 g of 4,4'-bipyridine and 150 g of 2-methylimidazole were dissolved in 2200 g of ethanol, reacted at 80° C. for 30 h to obtain a precipitate, which was centrifuged and washed three times. After vacuum drying at 60° C., Fe / Co-MOFs (i.e., metal organic framework materials) were obtained.
[0098] (2) Weigh 40 g of the Fe / Co-MOFs obtained in step (1), 5 g of polyvinylidene fluoride, 2 g of polyvinyl pyrrolidone and 16 g of polyacrylonitrile, add them to 180 g of dimethylacetamide, stir at 70°C until uniformly dissolved to form a spinning solution, and prepare MOF-based nanofibers with a diameter of 400 nm by high-voltage electrospinning.
[0099] (3) The MOF-based nanofibers obtained in step (2) were pre-oxidized in an air atmosphere at 275° C. for 0.8 h, and then melamine powder in a weight ratio of 1:3 was evenly sprinkled on the fibers, and heat-treated in a nitrogen atmosphere at 1300° C. for 2.2 h. After grinding and crushing, a metal / nitrogen co-doped integrated composite material of in-situ grown carbon nanotubes with a length of 38 μm, i.e., a metal / nitrogen composite material, was obtained.
[0100] (4) Weigh 3 g of the metal / nitrogen composite material obtained in step (3) and disperse it in 100 mL of isopropanol solution. Use a spray gun with a nozzle diameter of 0.3 mm, a spraying amount of 0.25 g / min, and a spraying time of 30 min to load the mixed solution onto a 6 cm×6 cm viscose-based carbon felt material with a thickness of 4.3 mm. After vacuum drying at 40° C., an electrode material with a loaded catalytic layer is obtained. The electrode material is assembled into a single cell and the charge and discharge performance is tested: at a current density of 120 mA / cm 2 When the current density is increased to 200mA / cm 2 When the power consumption is 2.04W, the energy efficiency is 80.9%, the voltage efficiency is 82.6%, and the coulombic efficiency is 97.9%.
[0101] Those skilled in the art should recognize that the above embodiments are only used to illustrate the present invention, and are not intended to limit the present invention. As long as they are within the spirit of the present invention, any changes or modifications to the above embodiments will fall within the scope of the claims of the present invention.
Claims
1. A method for preparing a carbon felt electrode with a catalyst layer for a flow battery electrode, characterized in that: The metal / nitrogen composite material is dispersed in an organic alcohol solution to obtain a mixed solution, and the mixed solution is loaded on a carbon felt substrate by a spraying method. After vacuum drying, a carbon felt electrode loaded with a catalytic layer for a liquid flow battery electrode is obtained.
2. The method for preparing a carbon felt electrode carrying a catalytic layer for a flow battery electrode according to claim 1, characterized in that: The volume ratio of the mass of the metal / nitrogen composite material to the organic alcohol solution is 0.02-0.04 g / ml; and / or The organic alcohol is selected from one of isopropanol, methanol, ethanol and n-butanol; and / or The carbon felt substrate is selected from one of PAN-based carbon fiber felt, asphalt-based carbon fiber felt, and viscose-based carbon fiber felt.
3. The method for preparing a carbon felt electrode carrying a catalytic layer for a flow battery electrode according to claim 1, characterized in that: The process parameters of the spraying are: nozzle diameter is 0.2-0.6 mm, spraying amount is 0.05-0.3 g / min, and spraying time is 20-80 min.
4. The method for preparing a carbon felt electrode carrying a catalytic layer for a flow battery electrode according to claim 1, characterized in that: The thickness of the carbon felt substrate is 2 to 5 mm; and / or The loading amount of the metal / nitrogen composite material on the carbon felt electrode supporting the catalytic layer for the liquid flow battery electrode is 5 to 15 mg / cm 2 .
5. The method for preparing a carbon felt electrode carrying a catalytic layer for a flow battery electrode according to claim 1, characterized in that: The metal / nitrogen composite material comprises the following steps: S1, dissolving a transition metal salt and an organic ligand in a solvent for reaction, and then sequentially centrifuging, washing and vacuum drying to obtain a metal organic framework material; S2, adding the metal organic framework material and polymer powder obtained in step S1 into an organic solvent, stirring until uniformly dissolved to form a spinning solution, and preparing a MOF-based nanofiber membrane by high-voltage electrospinning; S3, pre-oxidizing the MOF-based nanofiber membrane, heat-treating it with melamine powder, grinding it and breaking it, to obtain a metal / nitrogen co-doped integrated composite material of in-situ grown carbon nanotubes, that is, a metal / nitrogen composite material.
6. The method for preparing a carbon felt electrode carrying a catalytic layer for a flow battery electrode according to claim 5, characterized in that: In step S1: The transition metal salt is selected from one or more of zinc nitrate, zinc sulfate, zinc chloride, zinc acetate, cobalt nitrate, cobalt sulfate, cobalt chloride, cobalt acetate, nickel nitrate, nickel sulfate, nickel chloride, nickel acetate, ferric nitrate, ferric sulfate, ferric chloride, and ferric acetate; and / or The organic ligand is selected from one or more of 2-methylimidazole, 4,4'-bipyridine, o-phenanthroline, 2,3,5-pyridine triacid and terephthalic acid: and / or The solvent is selected from one or more of methanol, water, ethanol and dimethylformamide; and / or The transition metal salt and the organic ligand are dissolved in 3 to 20 parts by weight of a solvent at a weight ratio of 1:0.5 to 1:5; and / or The reaction temperature is 20-200° C., and the reaction time is 2-48 hours.
7. The method for preparing a carbon felt electrode carrying a catalytic layer for a flow battery electrode according to claim 6, characterized in that: In step S1: The transition metal salt and the organic ligand are dissolved in 5 to 15 parts by weight of a solvent at a weight ratio of 1:1 to 1:3; and / or The reaction temperature is 20-150° C., and the reaction time is 6-36 hours.
8. The method for preparing a carbon felt electrode carrying a catalytic layer for a liquid flow battery electrode according to claim 5, characterized in that: In step S2: The polymer powder is selected from one or more of polyacrylonitrile, polyimide, polyvinylidene fluoride and polyvinyl pyrrolidone; and / or The organic solvent is selected from one of dimethylformamide, dimethyl sulfoxide and dimethylacetamide; and / or The metal organic framework material and the polymer powder are mixed in a weight ratio of 0.1:1 to 5:1 and then added to 1 to 10 parts by weight of an organic solvent; and / or The stirring temperature is 20 to 100° C.; and / or The diameter of the MOF-based nanofiber membrane is 50 to 800 nm.
9. The method for preparing a carbon felt electrode carrying a catalytic layer for a liquid flow battery electrode according to claim 8, characterized in that: In step S2: The metal organic framework material and the polymer powder are mixed in a weight ratio of 0.5:1 to 3:1 and then added to 2 to 5 parts by weight of an organic solvent; and / or The stirring temperature is 40 to 80° C.; and / or The diameter of the MOF-based nanofiber membrane is 100-600 nm.
10. The method for preparing a carbon felt electrode carrying a catalytic layer for a liquid flow battery electrode according to claim 5, characterized in that: In step S3: The pre-oxidation treatment process is carried out in an air atmosphere, the pre-oxidation temperature is 180 to 300° C., and the pre-oxidation time is 0.5 to 5 hours; and / or The weight ratio of the pre-oxidized MOF-based nanofiber membrane to the melamine powder is 1:0.2 to 1:5; and / or The heat treatment is carried out in a nitrogen atmosphere, the heat treatment temperature is 600 to 2500° C., and the heat treatment time is 0.5 to 4 hours; and / or The heat treatment method of the pre-oxidized MOF-based nanofiber membrane and the melamine powder is one of uniform spreading, parallel arrangement and vertical arrangement; and / or The length of the metal / nitrogen composite material is 1 to 60 μm.
11. The method for preparing a carbon felt electrode carrying a catalytic layer for a liquid flow battery electrode according to claim 10, characterized in that: In step S3: In the pre-oxidation treatment, the pre-oxidation temperature is 200 to 280° C. and the pre-oxidation time is 1 to 4 hours; and / or The weight ratio of the pre-oxidized MOF-based nanofiber membrane to the melamine powder is 1:0.5 to 1:4; and / or During the heat treatment, the heat treatment temperature is 800-2200° C. and the heat treatment time is 1-3 hours; and / or The length of the metal / nitrogen composite material is 5 to 50 μm.
12. A carbon felt electrode for a liquid flow battery electrode carrying a catalytic layer, prepared according to the method for preparing a carbon felt electrode for a liquid flow battery electrode according to any one of claims 1 to 11.
13. Use of the carbon felt electrode carrying a catalytic layer for a liquid flow battery electrode according to claim 12 in a liquid flow battery.
14. The use according to claim 13, characterized in that: At a current density of 120 mA / cm 2 When the carbon felt electrode with a catalytic layer for the flow battery electrode has an energy efficiency of ≥83%, a voltage efficiency of ≥85%, and a coulombic efficiency of ≥95%; and / or At a current density of 200 mA / cm 2 When the carbon felt electrode with a catalytic layer for the liquid flow battery electrode is used, the energy efficiency is ≥80%, the voltage efficiency is ≥82%, and the coulombic efficiency is ≥94%.
Citation Information
Patent Citations
A porous electrode for flow batteries and its preparation method
CN111785978B
Cited By
Modified flow battery electrode capable of simultaneously improving activity and stability and preparation method of modified flow battery electrode
CN119674107A
Nitrogen-doped porous carbon electrode material and preparation method and application thereof
CN120328535A
Composite electrode with built-in lappet-connected diversion trench, preparation method and application of composite electrode in flow battery
CN120854573A
